Accuracy of faecal occult blood test and Helicobacter pylori stool antigen test for detection of upper gastrointestinal lesions. Issue 10 (30th October 2013) - Lee, Yi-Chia; Chiu, Han-Mo; Chiang, Tsung-Hsien; Yen, Amy Ming-Fang; Chiu, Sherry Yueh-Hsia; Chen, Sam Li-Sheng; Fann, Jean Ching-Yuan; Yeh, Yen-Po; Liao, Chao-Sheng; Hu, Tsung-Hui; Tu, Chia-Hung; Tseng, Ping-Huei; et al.
Abstract : Objective: Highly sensitive guaiac-based faecal occult blood (Hemoccult SENSA) and Helicobacter pylori stool antigen testing might help detect upper gastrointestinal lesions when appended to a colorectal cancer screening programme with faecal immunochemical testing. We evaluated the diagnostic accuracies of two stool tests in detecting upper gastrointestinal lesions. Design: Cross-sectional design. Setting: Hospital-based and community-based screening settings. Participants: A hospital-based deviation cohort of 3172 participants to evaluate test performance and a community-based validation cohort of 3621 to verify the findings. Interventions: Three types of stool tests with bidirectional endoscopy as the reference standard. Outcomes: Sensitivity, specificity and positive and negative likelihood ratios. Results: For detecting upper gastrointestinal lesions in cases with negative immunochemical tests, the sensitivity, specificity, and positive and negative likelihood ratios of the guaiac-based and H pylori antigen tests were 16.3% (95% CI 13.3% to 19.8%), 90.1% (88.9% to 91.2%), 1.64 (1.31 to 2.07), and 0.93 (0.89 to 0.97), respectively, and 52.5% (48.1% to 56.9%), 80.6% (79.0% to 82.1%), 2.71 (2.41 to 3.04) and 0.59 (0.54 to 0.65), respectively. For detecting upper gastrointestinal lesions in cases with normal colonoscopy, the results of the guaiac-based and H pylori antigen tests were 17.9% (14.8% to 21.5%), 90.1% (88.9% to 91.2%), 1.81 (1.45 to 2.26) and 0.91 (0.87 to 0.95), respectively, and 53.1% (48.6% to 57.4%), 80.7% (79.1% to 82.2%), 2.75 (2.45 to 3.08) and 0.58 (0.53 to 0.64), respectively. Within the community, positive predictive values of the immunochemical and H pylori antigen tests were 36.0% (26.0% to 46.0%) and 31.9% (28.3% to 35.5%), respectively, for detecting lower and upper gastrointestinal lesions, which were similar to expected values. Conclusions: The H pylori stool antigen test is more accurate than the guaiac-based test in the screening of upper gastrointestinal lesions in a population with high prevalence of H pylori infection and upper gastrointestinal lesions. It is applicable to add the H pylori antigen test to the immunochemical test for pan detection. Trial registration: NCT01341197 (ClinicalTrial.gov).